Voting transparency and conflicting interests in central bank councils - Gersbach, Hans; Hahn, Volker (Discussion paper, 2001)
This paper examines whether it is socially desirable for the individual voting records of central bank council members to be published when central bankers' preferences differ. We show that the misrepresentation of their preferences is not advantageous for central bankers although central bankers take into account the fact that they might not be re-elected. Thus, the publication of voting records is beneficial since the government can distinguish central bankers in terms of their preferences and can align the central bank council's preferences with those of the general public over time by means of its re-election decisions.